Evaluation of Different Autologous Platelet Concentrate Biomaterials: Morphological and Biological Comparisons and Considerations - Marchetti, Enrico (Materials (Basel), 2020)
The field of regeneration interventions in oral and maxillofacial surgeries still represents a challenge for researchers and clinicians. Understanding the biological and morphological behaviour of human cells towards the materials used for the regeneration surgeries is key to successfully choosing and applying the appropriate biomaterials for specific clinical situations. The aim of the study was the biological and morphological evaluation of autologous platelet concentrate materials obtained with different protocols, in culture with human periodontal ligament fibroblasts (HPLF). The study design included the evaluation of Leukocyte-Platelet-Rich-Fibrin (L-PRF), Concentrated Growth Factors (CGF) and autologous platelet gel (APG) in contact with the HPLF cell line after 24 h, 72 h and 7 days of in vitro culture. Cell proliferation and, therefore, viability were evaluated with XTT assays. The morphological response of the cells was evaluated by light microscopy, scanning electron microscopy and confocal microscopy. The XTT assay showed an interesting response in the growth curve. In particular, the material that gave the best results was the CGF. The morphological data supported the XTT assay, showing the best results for the CGF and L-PRF. In conclusion, all the platelet-derived materials stimulated the onset of the growth of the HPLF cell line, making them promising options for periodontal regeneration interventions.